Tissue Engineering A Primer with Laboratory Demonstrations - Yoon, Jeong-Yeol.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Tissue Engineering: A Primer with Laboratory Demonstrations concisely covers the fundamental basics of tissue engineering. A series of simple, low-cost, and easy-to-implement laboratory modules are included in each chapter, along with experimental results with actual images and data, and a set of questions and discussion topics for each laboratory exercise. The textbook is appropriate for upper-undergraduate and graduate-level courses in cell and tissue engineering. The inclusion of images and data for all laboratory exercises also makes the book a valuable tool for scientists and engineers to learn the concepts in a hands-on and visual manner and lay a foundation to build their experiments towards their research and commercial development. Concisely covers the most up-to-date aspects of tissue engineering; Provides step-by-step learning of all necessary concepts; Includes simple, low-cost, and easy-to-implement laboratory exercises.
Chapter 1. Introduction -- Chapter 2. Cell Culture -- Chapter 3. Cell Metabolism -- Chapter 4. Cell Imaging -- Chapter 5. Stem Cells -- Chapter 6. Biomaterial Surfaces -- Chapter 7. Focal Adhesion -- Chapter 8. Contact Guidance and Cell Patterning -- Chapter 9. 3D Scaffold Fabrication -- Chapter 10. Design of In Vitro Culture and Bioreactor -- Chapter 11. Organ-on-a-Chip -- Chapter 12. Tissue-Engineered Skin Transplant -- Chapter 13. Vascularization of Tissue Transplants -- Chapter 14. Advances Topics.
Keywords: Biomedical engineering; Regenerative medicine; Cytology; Biotechnology; Biomedical Engineering and Bioengineering; Regenerative Medicine and Tissue Engineering; Cell Biology; Biotechnology; Tissue Engineering